Going beyond Numbers to Complicate the Given Information: Elementary Children’s Mathematical Writing - Kosko, Karl W. (Pump It Up, 2016)
Elementary aged children need developmentally appropriate activities to engage them in argumentative writing in mathematics (math writing).